ANALYTICAL MODELING OF ADDITIONALLY ACQUIRED KNOWLEDGE OF THE LEARNING PROCESS WITH THE HELP OF AN INTELLECTUAL SYSTEM - Халдаров Хикматулла Ахматович (Galaxy International Interdisciplinary Research Journal, 2023)
This work is devoted to the study of the quality of the learning process by management in the acquisition of additional knowledge using analytical modeling and the use of ergonomics. Where, the issue of the learning process is considered, with the participation of additional sources of information - an intelligent system (IS) in the acquisition of knowledge by the trainee.